Enhancing EFL Learner Autonomy through Project-Based Learning: The Case of Secondary School Students - Insaf Khoudri; Abderrafii Khoudri; Mohammed Zeriouh (Yayasan Visi Intan Permata, 2023)
With the 21st century constant changes and demands, heated debate on ways to enhance Moroccan EFL students’ autonomy has sparked the interest of stakeholders. Although learner-centered teaching has been recommended in the past few years, teacher-centered instructional styles are; however, predominating in real teaching-learning practices. Autonomous learning skills and self-directed learning are needed in the twenty-first century, and project-based learning is a way to respond to that requirement. The purpose of this paper is to investigate if project-based learning could enhance the autonomy of learners in a Moroccan EFL context. Similarly, this research aims at interviewing the presenters’ peers on their performance; a method whereby they could develop critical thinking skills. To achieve this purpose, data was collected through a self-assessment questionnaire and a semi-structured interview. The participants were a classroom of 17 Secondary (2nd baccalaureate) school students. Results demonstrated that project-based learning enhances learner autonomy and responded to the demands of the 21st century skills. Likewise, based on the findings, learners managed to improve their autonomy during the implementation of project-based learning, and levels of autonomy vary among learners. Future researchers need to take into consideration that not all learners maintain a positive view concerning project-based learning perhaps they are accustomed to teacher spoon-fed and hand hold; consequently, they become passive. To deal with this dilemma, teachers had better remind students repeatedly that project-based learning contributes in boosting their autonomy and prepares them for the post-graduation exigencies.